Behavioral indicators of cattle housed in different shade surfaces availability completed in dry tropical environment - Castro-Pérez, B. I.; Portillo-Loera, J. J.; Estrada-Angulo, A.; Urías-Estrada, J. D.; Rivera-Méndez, C. R.; Mendoza-Cortez, D. A.; Plascencia, A.; Ríos-Rincon, F. G. (Journal of the Indonesian Tropical Animal Agriculture, 2026)
The objective was to assess the behavioral indicators of cattle housed in different shade surface availabilities under dry tropical environmental conditions carried out in the summer-autumn period. During 63 days the usual social and agonist variables were recorded in 1,040 bulls housed in 16 pens (4 replicas/treatment, 65 bulls/pen). Ambient temperature (AT) and relative humidity (RH) were record-ed, and the humidity index (THI) was estimated. The shade surfaces tested were 1) conventional shade (S12%), 2) double shade (S24%), 3) shaded 100% without fans (S100), and 4) shaded 100% with fans (S100F). The average maximum value for AT, RH and THI was 38.1°C, 90.7% and 87.6 units. The shade surface influenced the proportion of animals under shade, eating, ruminating, and mounting, and decreased the proportion of animals panting. Pens S24 showed a higher proportion of animals eating and resting (quadratic component, P=0.05). Providing ventilation increased (P=0.01) 2.7 times the pro-portion of animals eating and decreased (P=0.01) 6.5 times the proportion of animals panting. At 0800h a greater proportion of animals eating and riding was observed, while from 1130h onwards the proportion of animals under shade, ruminating and resting increased. At 2:00 p.m., the highest percent-age of animals were panting. It is concluded that  a shaded surface of 12% of the pen area is enough to alleviate behavioral patterns in animals under high environmental heat load. Shade plus ventilation was shown to be a strategy in reducing panting and increasing the proportion of animals in feed bunks.